PENGARUH MOTIVASI BELAJAR, PENYALAHGUNAAN TEKNOLOGI INFORMASI, DAN INTEGRITAS MAHASISWA TERHADAP PERILAKU KECURANGAN AKADEMIK MAHASISWA AKUNTANSI - Ni Made Dwi Surya Rahayu; Komang Krishna Yogantara; Laras Oktaviani (Journal Research of Accounting, 2023)
This study aims in this research to determine the effect of learning motivation, misuse of information technology and student integrity on academic cheating behavior. The population in this study were students of the accounting study program who studied at Triatma Mulya Badung University, totaling 237 students, with a sample of 119 respondents. The data collection method used is a questionnaire. The data analysis technique used in this study is multiple linear regression, coefficient of determination, F test and t test. Based on the results of the study it can be seen that learning motivation has a negative and significant effect on academic cheating behavior, misuse of information technology has a significant positive effect on academic cheating behavior and student integrity has a significant negative effect on academic cheating behavior. The magnitude of the influence of learning motivation variables, information technology abuse and student integrity on academic fraud behavior is 54.3%. Suggestions that can be given by researchers are that Triatma Mulya University is expected to provide motivation to students during learning, to increase student learning motivation